In the face of consciousness: how emotion, orientation, and gaze modulate face perception - Lanfranco Guevara, Renzo Carlo (The University of Edinburgh, 2020)
Human faces convey essential information for social behaviour, such as information about others’ mental states and intentions. Crucially, many studies have claimed that several facial features such as configural facial information, emotional expressions, and gaze direction modulate how faces gain access to perceptual awareness. However, the procedures employed in said studies suffer from multiple methodological issues and limitations. In a series of experiments, I tested whether configural facial features, emotional expressions, and gaze direction modulate how faces gain access to awareness. To achieve this, I used stringent procedures that allow measurement of perceptual sensitivity and decision criterion to the location and identity of faces. I used these measures to assess how long it takes faces to reach awareness as they overcome Continuous Flash Suppression – an interocular suppression technique that can render images invisible for several seconds. Using classical and Bayesian analyses, I found that configural face processing (which occurs for upright, but not inverted faces) promotes faces’ access to awareness. Similarly, faces making eye contact gain access to awareness faster than faces looking away. Contrary to past claims, however, I found that faces expressing negative emotional expressions (anger or fear) do not enter awareness faster than neutral expressions. In another series of experiments, I measured the minimal exposure durations required for configural facial processing, emotion processing, metacognition, and conscious access. To this end, I used a newly developed LCD tachistoscope that can present images with sub-millisecond precision and examined both behavioural (psychophysical) and neural (electroencephalography) markers of processing. I found that configural face processing promotes faces’ access to awareness by showing that upright faces require shorter exposure durations than inverted faces to be seen. Crucially, only around four milliseconds of exposure were required to find this advantage. Fearful expressions, however, do not gain access to awareness faster than neutral expressions. Evidence from neural markers expanded this by showing that the exposure duration required for configural facial processing is the same as that required for faces to reach conscious access. Finally, around six milliseconds of exposure were required for emotion processing. Together, these findings shed light on the factors that affect access of faces to awareness: configural facial information and gaze direction can modulate faces’ access to perceptual awareness; and such modulation is due to perceptual sensitivity rather than decision criterion. Furthermore, the perceptual processing of faces follows a hierarchical pattern: configural information precedes and facilitates access to awareness, and emotion processing follows awareness.
Keywords: consciousness; face perception; emotion processing; visual perception; EEG; psychophysics; interocular suppression; unconscious processing; perceptual awareness